2022
DOI: 10.3390/foods11243995
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Pectin from Passion Fruit Peel: Composition, Structural Characterization and Emulsion Stability

Abstract: Extraction methods directly affect pectin extraction yield and physicochemical and structural characteristics. The effects of acid extraction (AE), ultrasonic-assisted acid extraction (UA), steam explosion pretreatment combined with acid extraction (SEA) and ultrasonic-assisted SEA (USEA) on the yield, structure, and properties of passion fruit pectin were studied. The pectin yield of UA was 6.5%, equivalent to that of AE at 60 min (5.3%), but the emulsion stability of UA pectin was poor. The pectin obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 50 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Moreover, it showed higher pectin extraction (10.7 %) and a low degree of esterification (68.5 %), but they exhibited lower thermal stability. The outcomes revealed that US steam explosion acid treatment was more effective and provided higher pectin yield [80] .…”
Section: Recovery Of Biomolecules From Food Wastementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it showed higher pectin extraction (10.7 %) and a low degree of esterification (68.5 %), but they exhibited lower thermal stability. The outcomes revealed that US steam explosion acid treatment was more effective and provided higher pectin yield [80] .…”
Section: Recovery Of Biomolecules From Food Wastementioning
confidence: 99%
“… [79] Passion fruit peel Pectin 480 W, 65 °C, 15 min Total yield 6.5 %. [80] Jackfruit pulp Phenols and antioxidants 15 min, 250 W, LS 1:30, solvent 60 % TPC 1.28 mg GAE/g (water extract), TPC 1.64 mg GAE/g (methanol extract), TPC 1.16 mg GAE/g (ethanol extract), TPC 1.57 mg GAE/g acetone extract, DDPH 28 % (water extract), DDPH 37 % (methanol extract), DDPH 27 % (ethanol extract), DDPH 25 % (acetone extract). [81] Jujube peels Flavonoids Ethanol 20 %, LS 1:30 g/mL, 200 W, 50 min TFC 7.05 mg/g.…”
Section: Recovery Of Biomolecules From Food Wastementioning
confidence: 99%
“…The peels can be used as fertilizer and fodder ( Sena et al, 2015 ). Several studies have reported the nutritional and functional values of edible pectin/polysaccharides and phenolic compounds extracted from passion fruit peels, which can be used as consistency agents and antioxidant components ( Liang et al, 2022 , da Costa et al, 2023 ).While passion fruit, in fact, contains 14.9 %–30.1 % oil( Fonseca, Geraldi, Junior, Silvestre, & Rocha, 2022 ). Depending on the diversity of species, regions, and climates, its seed oil is rich in unsaturated fatty acids, including linoleic acid (53.0–75.1 % (w/w) of total FA content), oleic acid (13.6–31.2 % (w/w) of total FA content), and smaller amounts of linolenic, palmitoleic, and gadoleic acids ( Fonseca et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional procedures, it is more efficient, as it reduces the extraction time and solvent amount and increases the extraction yields. In particular, steam explosion-assisted extraction has been shown to improve the extraction yields of polysaccharides, polyphenols, flavonoids, saponins and alkaloids, etc., from many types of medicinal and edible plants [ 14 , 15 , 16 , 17 , 18 ]. Our previous studies on the SE modification of wheat bran and apple pomace have confirmed that SE can promote the conversion of IDF to SDF and thus increase the extraction yield of SDF [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%